CONTEMPORARY ARAB MUSIC VIDEO CLIPS: BETWEEN SIMULATING MTV’S GENDER STEREOTYPES AND FOSTERING NEW ONES - Elouardaoui, Ouidyane (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
MTV was the first 24-hour cable network to continuously broadcast music videos in the 1980s, thus establishing the genre. Generally, Arab music video clips differ from Western-produced music videos, because artists are compelled to abide by the conservative cultural norms of Arab societies. However, most Arab music videos, particularly those produced in the last decade, reaffirm Western gender stereotypes intrinsic to those produced by MTV. Contemporary Arab music videos for the most part simulate an MTV aesthetic vocabulary of a gaze that features female sexuality and narratives of seduction. Some new Arab producers, nonetheless, have attempted to avoid reproducing MTV-based gender clichés, but have instead created new gender misconceptions. These productions emphasize depictions of women as untrustworthy and impetuous. Finally, I discuss how young Arab singers have constantly been confronted by the ire of regionally prominent religious figures who denounce the music videos’ endorsement of “anti-Islamic” principles. I contend that Stuart Hall and Paddy Whannel’s early analysis of reactions against popular music styles among British youth as a form of cultural transgression remains relevant to understanding the cultural style of Arab youth as expressed through popular musical performance.